2017
DOI: 10.1158/0008-5472.can-16-3413
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinating Enzyme USP9X Suppresses Tumor Growth via LATS Kinase and Core Components of the Hippo Pathway

Abstract: The core LATS kinases of the Hippo tumor suppressor pathway phosphorylate and inhibit the downstream transcriptional coactivators YAP and TAZ, which are implicated in various cancers. Recent studies have identified various E3 ubiquitin ligases that negatively regulate the Hippo pathway via ubiquitination, yet few deubiquitinating enzymes (DUB) have been implicated. In this study, we report the DUB USP9X is an important regulator of the core kinases of this pathway. USP9X interacted strongly with LATS kinase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 40 publications
1
61
0
Order By: Relevance
“…19,36,37 For example, elevated expression of USP9X has been documented in several types of human cancers, including non-small-cell lung cancer, esophageal squamous cell carcinoma, B-cell lymphoma, cervical carcinoma, and melanoma, and its high expression is closely linked with tumor growth, invasion, metastasis, and chemoresistance. 26,36,[38][39][40][41][42][43] Conversely, USP9X has tumor suppressor functions in pancreatic ductal adenocarcinoma 37,44,45 and colorectal cancer. 46 Interestingly, 2 recent studies showed that USP9X stabilizes large tumor suppressor kinase 2, an upstream component of the Hippo pathway, to negatively regulate YAP and its target genes to suppress tumor growth in pancreatic 44,45 and breast 44 cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,36,37 For example, elevated expression of USP9X has been documented in several types of human cancers, including non-small-cell lung cancer, esophageal squamous cell carcinoma, B-cell lymphoma, cervical carcinoma, and melanoma, and its high expression is closely linked with tumor growth, invasion, metastasis, and chemoresistance. 26,36,[38][39][40][41][42][43] Conversely, USP9X has tumor suppressor functions in pancreatic ductal adenocarcinoma 37,44,45 and colorectal cancer. 46 Interestingly, 2 recent studies showed that USP9X stabilizes large tumor suppressor kinase 2, an upstream component of the Hippo pathway, to negatively regulate YAP and its target genes to suppress tumor growth in pancreatic 44,45 and breast 44 cancer.…”
Section: Discussionmentioning
confidence: 99%
“…26,36,[38][39][40][41][42][43] Conversely, USP9X has tumor suppressor functions in pancreatic ductal adenocarcinoma 37,44,45 and colorectal cancer. 46 Interestingly, 2 recent studies showed that USP9X stabilizes large tumor suppressor kinase 2, an upstream component of the Hippo pathway, to negatively regulate YAP and its target genes to suppress tumor growth in pancreatic 44,45 and breast 44 cancer. In contrast, another study reported that USP9X deubiquitinates and stabilizes YAP1, a major downstream effector of the Hippo pathway, thus promoting breast cancer cell survival and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Increased USP9X expression significantly up-regulates and stabilizes LATS and leads to a decrease in the transport of YAP/TAZ into the nucleus as well as inhibiting of their target genes. Furthermore, the expression level of USP9X is positively related to LATS expression but negatively associated with the expression of YAP/TAZ in multiple tumor tissues, such as pancreatic cancer and breast cancer, demonstrating that USP9X potentiates LATS kinase in suppressing tumor growth (Toloczko et al, 2017). …”
Section: The Roles Of Usps In Cancermentioning
confidence: 99%
“…Overexpression of YOD1 leads to enhanced hepatocyte proliferation and hepatomegaly in a YAP-dependent manner in a transgenic mouse model, and a strong connection exists between YOD1 and YAP expression in patients with liver cancer, which implies that YOD1 may promote tumor initiation (155). In comparison, USP9X (FAM) deubiquitinates LATS kinases to suppress tumor growth (156). The DUB3 family of deubiquitinating enzymes, which includes 25 USP17-like proteins, was identified, using a short hairpin RNA-based screening technique, to be a mediator of YAP/TAZ activity (157,158).…”
Section: Ubiquitination-deubiquitination In the Hippo Pathwaymentioning
confidence: 99%